2017
DOI: 10.1111/1475-679x.12177
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowers and Outcomes of Financial Misrepresentation Enforcement Actions

Abstract: Whistleblowers are ostensibly a valuable resource to regulators investigating securities violations, but whether there is a link between whistleblower involvement and the outcomes of enforcement actions is unclear. Using a data set of employee whistleblowing allegations obtained from the U.S. government and the universe of enforcement actions for financial misrepresentation, we find that whistleblower involvement is associated with higher monetary penalties for targeted firms and employees and with longer pris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 38 publications
6
65
0
Order By: Relevance
“…Wilde [2017] finds that external WB reports deter financial misreporting and tax aggressiveness for up to two years after a report is made. Furthermore, Call et al [2018] conclude that the involvement of an external whistleblower is associated with more severe penalties resulting from investigations by the Securities and Exchange Commission and Department of Justice, which could explain why firms involved in financial reporting violations grant more stock options to rank-and-file employees (Call, Kedia, and Rajgopal [2016]). Berger and Lee [2019] find a reduction in the likelihood of accounting fraud following the passage of the Dodd-Frank Act's WB incentive program, especially for firms in states that had previously not been subject to a state-level False Claims Act.…”
Section: Research On Whistleblowing and Whistleblower Regulationsmentioning
confidence: 99%
“…Wilde [2017] finds that external WB reports deter financial misreporting and tax aggressiveness for up to two years after a report is made. Furthermore, Call et al [2018] conclude that the involvement of an external whistleblower is associated with more severe penalties resulting from investigations by the Securities and Exchange Commission and Department of Justice, which could explain why firms involved in financial reporting violations grant more stock options to rank-and-file employees (Call, Kedia, and Rajgopal [2016]). Berger and Lee [2019] find a reduction in the likelihood of accounting fraud following the passage of the Dodd-Frank Act's WB incentive program, especially for firms in states that had previously not been subject to a state-level False Claims Act.…”
Section: Research On Whistleblowing and Whistleblower Regulationsmentioning
confidence: 99%
“…He tests (and rejects) the claim that private litigation linked to the False Claim Act and whistleblower rewards is ine¢ ciently dominated by a few, repeat, "professional" plainti¤-relators, and …nds that specialized legal …rms appear to play a positive role helping to unveil larger frauds than less experienced ones. 11 Call et al (2017) analyzes OSHA claims between 2002 and 2010 and …nds that whistleblowers'involvement in …nancial misrepresentation enforcement actions is correlated with higher monetary sanctions for the wrongdoing …rm and increased jail time for culpable executives, and that when whistleblowers are involved enforcement proceedings begin quicker. It also …nds that whistleblower involvement signi…cantly increases the likelihood that criminal sanctions are imposed.…”
Section: Related Literaturementioning
confidence: 99%
“…Table 1 presents a summary of the design dimensions. More recently, Call et al (2017) examined empirically the link between whistleblowing and (i) penalties, (ii) prison sentences, and (iii) duration of regulatory enforcement actions for financial misrepresentation. They found that whistleblowers' involvement in financial misrepresentation enforcement actions is correlated with higher monetary sanctions for the wrongdoing firm and increased jail time for culpable executives.…”
Section: Design Dimensions Of Reward Programsmentioning
confidence: 99%